Process simulation and performance optimization for the oxidation ditch sewage treatment plant in Baguio City through the application of IAWQ activated sludge model - Dulay, Josephine Aries L. (2002)
The organic and nitrogen impurities removal of the oxidation ditch of Baguio City Sewage Treatment Plant was investigated through the application of the Activated Sludge Model No. 1 in the Activated Sludge Simulation Program. Detailed wastewater characterization is necessary to produce accurate estimates of process performance. The ASM authors recommended the methods used in the characterization of wastewater. The inert particulate organic matter, Xi, inert soluble organic matter Si, readily biodegradable substrate Ss, Slowly biodegradable substrate Xs, and heterotrophic biomass Xh, were determined experimentally with values 12.01 to 13.05% Xi, 10.20% Si, 24.24% Ss, 43.06 to 44.10% Xs and 9.45% Xh. The wastewater component fractions of Baguio Citiy where within range estimated by the Inhternational Association of Water Quality (IAWQ) used in ASM 1 with values 15% Xi, 10% Si, 25% Ss, and 45% Xs. A few of the stoichiometric and kinetic coefficients were experimentally determined. These were the heterotrphic yield, Yh, maximum specific grownth rate of heterotrophs u^h and and heterotrophic decay coefficient bh with values of 0.638874,8.94 and 0.447 respectively. Likewise, the ASM authors recommended the methods used in the parameter determination.
ASM 1 was calibrated in order to optimize the performance of the full-scale plant. To fit the model to the observed results, only a few model parameters need to be changed. Aside from experimentally determined Yh and u^h, the maximum specific growth rate of autotrophs u^A with a value 0.9 and the saturation constant for soluble substrates, Ks with a value of 100, determined through simulation were changed. The values found were within the estimated range suggested by the ASM authors. IT was shown that the results of simulation agree with the observed results of the full-scale plant system. furthermore, validation of the model confirmed the evaluated stoichiometric and kinetic parameters indicating that the model mimicked the actual performance of the plant. The model has the ability to simulate a variety of possible scenarios observed in the full-scale performance of the wastewater treatment plant. The condition for optimum operation of the wastewater treatment plant for a high rate of nitrogen removal was found. THe effect of decreasing the dissolved oxygen concentration from 3.25 to 2 mg/L in the anoxic zone improved the rates of nitrificaton and denitrification in the ditch. Other scenarios showed the effect of changing the return sludge rate and the effect of shock loading when the return sludge valve was shut off intermittently but maintained the treatment efficiency of the ditch.
Thesis (M.S. Environmental Engineering)-- University of the Philippines, Diliman.
Keywords: Sewage -- Purification -- Activated sludge process -- Philippines -- Baguio City; Oxidation ditches -- Philippines -- Baguio City; Water treatment plant residuals -- Philippines -- Baguio City